Oil and gas prospects in deep deposits of the South Caspian water area - U. S. Serikova; M. A. Allanazarova (Известия высших учебных заведений: Геология и разведка, 2023)
Background. In this paper, we present the results of geological and geophysical works and an analysis of the conducted simulation of the South Caspian Basin.Aim. Simulation of hydrocarbon systems of the Turkmen sector of the South Caspian basin.Materials and methods. Statistical generalization and systematization of data and materials from reference literature, fund sources, field data and published works of Sh.F. Mekhtiev, I.S. Guliyev, M.Z. Rachinsky, S.S. Djibouti, S.A. Aliev, V.Yu. Kerimov, V.V. Kolodiya and others. Simulation was performed in the PetroMod software.Results. The conducted simulation showed that the entire commercial oil and gas potential in the region is positioned mainly outside the outer perimeter of the deep-water area, in the form of an annular strip with the width 20–50 km. All the deposits were found to be genetically and spatially associated with the areas of high macro- and micro-seismicity of slip joints filled with hydrothermal aggregates.